2017
DOI: 10.1371/journal.pntd.0005233
|View full text |Cite
|
Sign up to set email alerts
|

Cynomolgus macaques naturally infected with Trypanosoma cruzi-I exhibit an overall mixed pro-inflammatory/modulated cytokine signature characteristic of human Chagas disease

Abstract: BackgroundNon-human primates have been shown to be useful models for Chagas disease. We previously reported that natural T. cruzi infection of cynomolgus macaques triggers clinical features and immunophenotypic changes of peripheral blood leukocytes resembling those observed in human Chagas disease. In the present study, we further characterize the cytokine-mediated microenvironment to provide supportive evidence of the utility of cynomolgus macaques as a model for drug development for human Chagas disease.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…These findings may support, at least in part, the predominance of TcI infection amongst cynomolgus macaques in Southern part of the United States. Figures 4 and 5 present a synthesized scheme of our newest cytokine findings and reinforce the distinct cytokine pattern produced upon T. cruzi TcI and TcIV antigen recall in vitro [22]. Furthermore, other studies have confirmed the presence of both TcI and TcIV isolates from Amazonian primates, TcI being more predominate strain than TcIV [38][39][40].…”
Section: Immunological Features Of Nhp T Cruzi Infectionsupporting
confidence: 75%
See 4 more Smart Citations
“…These findings may support, at least in part, the predominance of TcI infection amongst cynomolgus macaques in Southern part of the United States. Figures 4 and 5 present a synthesized scheme of our newest cytokine findings and reinforce the distinct cytokine pattern produced upon T. cruzi TcI and TcIV antigen recall in vitro [22]. Furthermore, other studies have confirmed the presence of both TcI and TcIV isolates from Amazonian primates, TcI being more predominate strain than TcIV [38][39][40].…”
Section: Immunological Features Of Nhp T Cruzi Infectionsupporting
confidence: 75%
“…The infected animals exhibit higher frequency of NK Granzyme A + cells. Furthermore, this cell population was able to increase the pro-inflammatory cytokine secretion afterwards T. cruzi antigen stimulation [22]. These data reinforce the important role of NK cells as a source of IFN-γ to activate macrophages and increase the nitric oxide production to inhibit the intracellular parasite growth [23,24].…”
Section: Immunological Features Of Nhp T Cruzi Infectionsupporting
confidence: 62%
See 3 more Smart Citations